Warship under Sail : The USS Decatur in the Pacific West - McConaghy, Lorraine (Book collections on Project MUSE., 2009)
A social history of the nineteenth-century sloop of war "Decatur," that illuminates American expansionism in the antebellum Pacific Northwest